The Role of Mothers in the High Prevelance of Early Childhood Dental Caries: A Atudy Among Toddlers in the Peatland Areas of West Kalimantan - Sri Rezki; Pawarti; Fathiah; Dian Femala; Jojok Heru Susatyo (Gema Lingkungan Kesehatan, 2026)
Peatland environments often rely on groundwater with low mineral content, which may increase children’s vulnerability to dental caries. This study examined whether family factors parental education, occupation, economic status, and parenting practices are associated with dental caries among young children. This descriptive cross-sectional study used a mixed-methods approach. The study was conducted at PAUD Dzafira, East Pontianak, West Kalimantan, and included 45 parent–child pairs selected through total sampling. Data on parental characteristics, parenting practices, and children’s caries status were collected. Quantitative data were analyzed using Spearman’s correlation, and qualitative data were analyzed using NVivo. The mean dental caries score was 3.91 ± 3.21, ranging from 0 to 14 decayed teeth. Significant correlations were observed between children’s caries and maternal education (r = −0.452; p = 0.002), family economic status (r = −0.300; p = 0.045), and maternal occupation (r = −0.535; p < 0.001). Caries-free children were generally characterized by early habit formation, active parental supervision, and consistent motivation. In contrast, inconsistent routines, inappropriate toothbrushing times, and limited parental ability to teach toothbrushing behaviors were more common among children with caries. Higher maternal education, stable employment, and better economic conditions are associated with lower dental caries among children. Strengthening oral health education, especially for mothers as primary caregivers, and improving access to affordable dental care are essential to reduce caries risk in peatland communities.